A novel case of autosomal dominant cutis laxa in a consanguineous family: report and literature review. Issue 3 (July 2017) - Duz, Mehmet B.; Kirat, Emre; Coucke, Paul J.; Koparir, Erkan; Gezdirici, Alper; Paepe, Anne De; Callewaert, Bert; Seven, Mehmet
Abstract : Autosomal dominant cutis laxa (ADCL, OMIM #123700) is a rare connective tissue disorder characterized by loose, redundant skin folds that may be apparent form birth or appear later in life. Most severely affected areas are the neck, axillar regions, trunk, and groin. Typically, patients present with characteristic facial features including a premature aged appearance, long philtrum, a high forehead, large ears, and a beaked nose. Cardiovascular and pulmonary complications include bicuspid aortic valves, aortic root dilatation, and emphysema. Sporadically, these complications have been documented to cause premature death. Several rare findings including urogenital anomalies and gastroesophageal problems can be also occur. Most patients harbor a frameshift mutation in one of the five last exons of the ELN gene (ADCL1, OMIM #123700), whereas one patient was described to have a tandem duplication in the FBLN5 gene (ADCL2, OMIM #614434). Here, we present a female ADCL patient, from a consanguineous family, with a novel mutation in ELN and review 39 previously reported ADCL patients. All patients have various skin findings, whereas cardiovascular, pulmonary findings, and multiple hernia were present in 61, 28, and 38% of patients, respectively. Strabismus, urogenital anomalies, gastroesophageal problems, and scoliosis may rarely be present. A clear definition of the ADCL syndrome can enable more accurate genetic counseling.